K2P2.1 channels modulate the pH- and mechanosensitivity of pancreatic stellate cells - Micol Rugi; Verena Hofschröer; Zoltán Pethő; Benjamin Soret; Thorsten Loeck; Albrecht Schwab (Pflügers Archiv - European Journal of Physiology, 2025)
Pancreatic stellate cells (PSCs) are central in the development of acute pancreatitis and tumor fibrosis in pancreatic ductal adenocarcinoma (PDAC). Fibrosis and a unique pH landscape represent characteristic properties of the PDAC microenvironment. Mechanosensitive ion channels are involved in the activation of PSCs. Among these channels, K 2P 2.1 has not yet been studied in PSCs. K 2P 2.1 channels are pH- and mechanosensitive. We confirmed K 2P 2.1 expression in PSCs by RT-qPCR and immunofluorescence. PSCs from K 2P 2.1 +/+ and K 2P 2.1 −/− mice were studied under conditions mimicking properties of the PDAC microenvironment (acidic extracellular pH (pH e ), ambient pressure elevated by + 100 mmHg). Migration and the cell area were taken as surrogates for PSC activation and evaluated with live cell imaging. pH e -dependent changes of the membrane potential of PSCs were investigated with DiBAC 4 (3), a voltage-sensitive fluorescent dye . We observed a correlation between morphological activation and progressive hyperpolarization of the cells in response to changes in pH e and pressure. The effect was in part dependent on the expression of K 2P 2.1 channels because the membrane potential of K 2P 2.1 +/+ PSCs was always more hyperpolarized than that of K 2P 2.1 −/− PSCs. Cell migration velocity of K 2P 2.1 +/+ cells decreased upon pressure application when cells were kept in an acidic medium (pH e 6.6). This was not the case in K 2P 2.1 −/− PSCs. Taken together, our study highlights the critical role of K 2P 2.1 channels in the combined sensing of environmental pressure and pH e by PSCs and in coordinating cellular morphology with membrane potential dynamics. Thus, K 2P 2.1 channels are important mechano-sensors in murine PSCs.

Correction to: The context‑dependent role of the Na+/Ca2+‑exchanger (NCX) in pancreatic stellate cell migration - Thorsten Loeck; Micol Rugi; Luca Matteo Todesca; Paulina Kalinowska; Benjamin Soret; Ilka Neumann; Sandra Schimmelpfennig; Karolina Najder; Zoltán Pethő; Valerio Farfariello; Natalia Prevarskaya; Albrecht Schwab (Pflügers Archiv - European Journal of Physiology, 2024)

The context-dependent role of the Na+/Ca2+-exchanger (NCX) in pancreatic stellate cell migration - Thorsten Loeck; Micol Rugi; Luca Matteo Todesca; Paulina Kalinowska; Benjamin Soret; Ilka Neumann; Sandra Schimmelpfennig; Karolina Najder; Zoltán Pethő; Valerio Farfariello; Natalia Prevarskaya; Albrecht Schwab (Pflügers Archiv - European Journal of Physiology, 2023)
Pancreatic stellate cells (PSCs) that can co-metastasize with cancer cells shape the tumor microenvironment (TME) in pancreatic ductal adenocarcinoma (PDAC) by producing an excessive amount of extracellular matrix. This leads to a TME characterized by increased tissue pressure, hypoxia, and acidity. Moreover, cells within the tumor secrete growth factors. The stimuli of the TME trigger Ca 2+ signaling and cellular Na + loading. The Na + /Ca 2+ exchanger (NCX) connects the cellular Ca 2+ and Na + homeostasis. The NCX is an electrogenic transporter, which shuffles 1 Ca 2+ against 3 Na + ions over the plasma membrane in a forward or reverse mode. Here, we studied how the impact of NCX activity on PSC migration is modulated by cues from the TME. NCX expression was revealed with qPCR and Western blot. [Ca 2+ ] i , [Na + ] i , and the cell membrane potential were determined with the fluorescent indicators Fura-2, Asante NaTRIUM Green-2, and DiBAC 4 (3), respectively. PSC migration was quantified with live-cell imaging. To mimic the TME, PSCs were exposed to hypoxia, pressure, acidic pH (pH 6.6), and PDGF. NCX-dependent signaling was determined with Western blot analyses. PSCs express NCX1.3 and NCX1.9. [Ca 2+ ] i , [Na + ] i , and the cell membrane potential are 94.4 nmol/l, 7.4 mmol/l, and − 39.8 mV, respectively. Thus, NCX1 usually operates in the forward (Ca 2+ export) mode. NCX1 plays a differential role in translating cues from the TME into an altered migratory behavior. When NCX1 is operating in the forward mode, its inhibition accelerates PSC migration. Thus, NCX1-mediated extrusion of Ca 2+ contributes to a slow mode of migration of PSCs.